BioCartilage Improves Cartilage Repair Compared With Microfracture Alone in an Equine Model of Full-Thickness Cartilage Loss - Fortier, Lisa A; Chapman, Hannah S; Pownder, Sarah L; Roller, Brandon L; Cross, Jessica A; Cook, James L; Cole, Brian J (The American journal of sports medicine, 2016)
Microfracture (MFx) remains a dominant treatment strategy for symptomatic articular cartilage defects. Biologic scaffold adjuncts, such as particulated allograft articular cartilage (BioCartilage) combined with platelet-rich plasma (PRP), offer promise in improving clinical outcomes as an adjunct to MFx. To evaluate the safety, biocompatibility, and efficacy of BioCartilage and PRP for cartilage repair in a preclinical equine model of full-thickness articular cartilage loss. Controlled laboratory study. Two 10-mm-diameter full-thickness cartilage defects were created in 5 horses in the trochlear ridge of both knees: one proximal (high load) and another distal (low load). Complete blood counts were performed on each peripheral blood and resultant PRP sample. In each horse, one knee received MFx with BioCartilage + PRP, and the other knee received MFx alone. Horses were euthanized at 13 months. Outcomes were assessed with serial arthroscopy, magnetic resonance imaging (MRI), micro-computed tomography (micro-CT), and histology. Statistics were performed using a mixed-effects model with response variable contrasts. No complications occurred. PRP generated in all subjects yielded an increase in platelet fold of 3.8 ± 4.7. Leukocyte concentration decreased in PRP samples by an average fold change of 5 ± 0.1. The overall International Cartilage Repair Society repair score in both the proximal and distal defects was significantly higher (better) in the BioCartilage group compared with MFx (proximal BioCartilage: 7.4 ± 0.51, MFx 4.8 ± 0.1, P = .041; distal BioCartilage: 5.6 ± 0.98, MFx 2.6 ± 1.5, P = .022). BioCartilage-treated proximal defects demonstrated improved histologic scores for repair-host integration (BioCartilage, 96 ± 9; MFx, 68 ± 18; P = .02), base integration (BioCartilage, 100 ± 0; MFx, 70 ± 37; P = .04), and formation of collagen type II (BioCartilage, 82 ± 8; MFx, 58 ± 11; P = .05) compared with the positive control. On MRI, T2 relaxation time was significantly shorter (better) in the superficial region of BioCartilage-treated distal defects compared with MFx (P = .05). There were no significant differences between BioCartilage and MFx on micro-CT analysis. BioCartilage with PRP safely improved cartilage repair compared with MFx alone in an equine model of articular cartilage defects up to 13 months after implantation. The 1-year results of BioCartilage + PRP suggest that homologous allograft tissue provides a safe and effective augmentation of traditional MFx.